Evaluation of the diagnostic value of the Modified Evan’s Blue Dye Test for assessing aspiration in tracheostomized critically ill patients: A systematic review and meta-analysis - Eszter Szőke; Ildikó Szántó; Caner Turan; Bence Szabó; Márton Papp; Gábor Horváth; László Zubek; Péter Hegyi; Zsolt Molnár; András Lovas (PLoS ONE, 2026)
Dysphagia and aspiration are common complications in tracheostomized critically ill patients. The Modified Evan’s Blue Dye Test (MEBDT) is a non-invasive, bedside, adjunctive rule-in signal for aspiration when positive. However, its diagnostic accuracy compared to the gold standard Fiberoptic Endoscopic Evaluation of Swallowing (FEES) in these patients remains unclear. We conducted a systematic review and meta-analysis to evaluate the diagnostic accuracy of the MEBDT for the detection of aspiration in tracheostomized critically ill patients. Study protocol was prospectively registered on PROSPERO (CRD:42023479920). A systematic search was performed across three databases (PubMed, Cochrane Central, and Embase), followed by a systematic screening process against predetermined selection criteria and included studies that provided data on the sensitivity and specificity of MEBDT versus FEES. The risk of bias and the level of evidence certainty in the included papers were assessed by the QUADAS-2 tool and GRADE approach respectively. Six out of 2227 screened studies were included. We found that MEBDT had a high specificity 95.42% (95% CI [67.38%, 99.53%]) and positive predictive value 95% (95% CI [81, 100]). In conclusion, the MEBDT can serve as a bedside adjunctive tool that indicates a potential aspiration risk when the result is positive. However, if the result is negative, further diagnostic assessments, like FEES, are recommended for high-risk patients.